2018
DOI: 10.1186/s12936-018-2357-7
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of malaria diagnosis and treatment for fever episodes according to patient history and anti-malarial blood measurement: a cross-sectional survey from Tanzania

Abstract: BackgroundMonitoring the impact of case management strategies at large scale is essential to evaluate the public health benefit they confer. The use of methodologies relying on objective and standardized endpoints, such as drug levels in the blood, should be encouraged. Population drug use, diagnosis and treatment appropriateness in case of fever according to patient history and anti-malarials blood concentration was evaluated.MethodsA cross-sectional survey took place between May and August 2015 in three regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…We could not detect an effect of drugs availability in HFs on antimalarial use since all HFs visited during the survey had ACTs in stock. However, the significant effect of stocks of ACTs in DSs shows the importance of these providers, as often reported in the literature [ 29 , 41 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We could not detect an effect of drugs availability in HFs on antimalarial use since all HFs visited during the survey had ACTs in stock. However, the significant effect of stocks of ACTs in DSs shows the importance of these providers, as often reported in the literature [ 29 , 41 ].…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies conducted in Tanzania reported that around 2.0% of the fever in low and 8–20% in highly endemic settings ([ 47 49 ] Boillat et al , unpublished) are due to malaria. In our study, 1021 individuals reported a fever in the previous two weeks (Tables 1 and 2 ), and 630 of them said they sought care because of their fever [ 29 ]. Considering that, on average, 10.0% of fevers are due to malaria according to literature, 63 individuals should have received an antimalarial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of adherence using blood concentration of piperaquine in intervention areas (as was done in the study by Morris et al) is welcome because it is known that self-reporting of medication intake is unreliable [10, 11]. However, it would have been useful to measure the blood concentration of a variety of antimalarials in both intervention and control areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, it would have been useful to measure the blood concentration of a variety of antimalarials in both intervention and control areas. Widespread unreported use of antimalarials (obtained from health facilities and private retailers) has been documented in Tanzania [11] and might have modified the effect of MDA rounds.…”
Section: Introductionmentioning
confidence: 99%